Isu Keberpihakan dalam Pemilihan Presiden 2024 (Analisis Framing Berita Makan Malam Jokowi dan Prabowo di Tempo.co Edisi 5 - 7 Januari 2024) - Kurniansyah, Rafli Akram; Mulyana, Deddy; Siregar, Rachmi Kurnia; Harningsih, Harningsih (LUGAS Jurnal Komunikasi, 2024)
The meeting between President Jokowi and Minister of Defense Prabowo at a dinner on January 5 2024, is suspected of Jokowi's political neutrality in the 2024 presidential election which is increasingly being questioned. This issue of partiality has been widely reported by online media, one of which is Tempo.co. The news selection was chosen on 5 - 7 January 2024 with the consideration that at that time the third presidential candidate debate would be held on 7 January 2024. So, the momentum of Jokowi and Prabowo's dinner was allegedly a form of covert support from President Jokowi for the presidential candidate Prabowo who will face the debate. This research uses a qualitative descriptive approach with a constructivist paradigm. Researchers framed news about Jokowi and Prabowo's dinner on Tempo.co using Robert N Entman's framing analysis method. The results of this research show that Tempo.co framed the issue of partiality in the 2024 presidential election in the Jokowi and Prabowo dinner news by reporting balanced information. This is proven by the existence of news information that contains pro and con parties in this report. This also shows that Tempo.co strives to maintain neutral news balance and has implemented Bill Kovach's journalistic elements of broadcasting comprehensive and proportional news.